Minder is meer. Die polisemantiese waarde van simbole - Wepener, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
As a whole this article explores the question whether a symbol may/must be explained or not. Therefore the Dutch liturgist Gerard Lukken’s distinction between sign and symbol, as well as his distinction between presentative and discursive symbolism, is firstly described. This is done in order to show that the meaning and functioning of a symbol should not be explained because of its unique nature as a symbol. A symbol is a poly-semantic and poly-active phenomenon, and any attempt at explanation limits and ultimately invalidates the functioning of a symbol. This position on the functioning of symbols is often criticised, and some Protestant theologians’ critique of this view is highlighted. If the meaning of a symbol may not be explained, how will it then be possible to establish whether a particular symbol is a Christian symbol or not? On the one hand this is a vital question for the specific way in which officiators use symbols and rituals in the liturgy, and on the other hand for the necessity/possibility of a criterion for the use of symbols and rituals in the Christian liturgy. In conclusion some guidelines in this regard is offered.